A lean approach of modeling the transient thermal characteristics of Loop Heat Pipes based on experimental investigations. (25th January 2019) - Meinicke, Sebastian; Knipper, Paul; Helfenritter, Christoph; Wetzel, Thomas
Highlights: Design of an experimental technique for thermal characterization of LHP. A physically sound numerical model describing the thermal behavior of different LHP. Matching experimental and numerical data by means of well-founded parameters. Calculation of stationary and transient operating states of the LHP. Validation of the proposed numerical approach for two different LHP setups. Abstract: A mathematical model capturing the steady-state and transient thermal characteristics of a Loop Heat Pipe (LHP) is presented. It is intended to provide valuable insights into the static and dynamic LHP system behavior, to be used e.g. for the design of sophisticated thermal control strategies by LHP end users. The model is set up in such a way, that its parameters are both physically meaningful and accessible to a determination based on a non-destructive and pragmatic experimental characterization of the considered LHP. The transient behavior of the LHP is predicted by the model based on separate calculation and update of the internal mass flow rates and phase distributions. It has been applied successfully to two different LHPs, as used in common satellite applications. Numerical results of the steady-state characteristics show an excellent agreement with corresponding experimental results, proving the reliability and transferability of the approach proposed. An in-depth transient analysis of one selected LHP is presented using characteristic heat load profiles, common for LHP space applications.